1958
DOI: 10.1002/aic.690040415
|View full text |Cite
|
Sign up to set email alerts
|

Radial porosity variations in packed beds

Abstract: The radial variation of void fraction in randomly packed beds of spheres, cylinders, Raschig rings, and Berl saddles was investigated. After packing, the beds were filled with parallln, which was then allowed to solidify. Slabs were cut from the bed, and annular rings were removed by two different experimental techniques. An analysis of experimental error revealed that reproducibility, for the sample size used, between different parts of the same bed and different beds was quite good.For highly irregular shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0

Year Published

1961
1961
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(94 citation statements)
references
References 2 publications
1
93
0
Order By: Relevance
“…Notable among them are the measurements of Furnas [14], Thierney et al [15], Schwartz and Smith [12] and Benenati and Brosilow [16 ]. Schwartz and Smith (1-+ be -c{/dp)…”
Section: Modell Der Geschwindigkeitsverteilung In Einem Isotherm Durcmentioning
confidence: 99%
“…Notable among them are the measurements of Furnas [14], Thierney et al [15], Schwartz and Smith [12] and Benenati and Brosilow [16 ]. Schwartz and Smith (1-+ be -c{/dp)…”
Section: Modell Der Geschwindigkeitsverteilung In Einem Isotherm Durcmentioning
confidence: 99%
“…Roblee et al [4] and Reyes and Iglesia [5] found that the porosity was affected in a region extending three grain diameters from a curved cylindrical wall in packs of monosized spheres. The results of Roblee et al [4] indicate that grain shape has a significant effect on the width of the boundary region, while Reyes and Iglesia's [5] results suggest that the width of the boundary region decreases as the grain size distribution is broadened.…”
Section: Introductionmentioning
confidence: 98%
“…This increase is confined within few particle diameters from the wail, Benenati (1962), Roblee (1958).…”
Section: Porosity Variationmentioning
confidence: 99%